Development of a droplet digital PCR assay for the detection of BK polyomavirus - Ai, Lu; Zhao, Yating; Tan, Chianru; Bai, Lu; Huang, Gang; Wang, Ruizhi; Huang, Hao; Yu, Xuegao; Guo, Yong; Chen, Peisong (Microbiology spectrum, 2024)
It was previously believed that droplet digital polymerase chain reaction had limitations, including high cost, limited throughput, and cumbersome operation, which hindered its widespread application in clinical practice. However, the current fully automated digital PCR platform, combined with streamlined operations, can detect 96 samples at once, and the entire process can be completed within an hour, laying a solid foundation for its extensive use.